For a,b,c non- zero, real distinct, the equation, ( a^2+b^2)x^2 -2b(a+c) x +b^2+c^2=0 has non-zero real roots. One of these roots is also the root of the equation? A) a^2x^2-a(b-c)x+bc=0 B) a^2x^2+a(c-b)x-bc=0 C) (b^2+c^2)x^2-2a(b+c)x+a^2=0

1 Answer
Mar 5, 2017

See below.

Explanation:

Solving for x in ( a^2+b^2)x^2 -2b(a+c) x +b^2+c^2=0 we have

x=(b (a + c) - sqrt[-(b^2 - a c)^2])/(a^2 + b^2) The solutions must be real so necessarily b^2 - a c=0 and the roots are real identical

x = {c/sqrt(ac),c/sqrt(ac)}

After substituting b = pmsqrt(ac) into the equations from A) to C)

we obtain for the option B) the roots

x = {c/sqrt(ac),c/a}

so the correct option is B)